2022
DOI: 10.1159/000521606
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Prostate Cancer Aggressiveness Using a Novel Multiparametric Magnetic Resonance Imaging Parameter: Tumor Heterogeneity Index

Abstract: <b><i>Background and Aims:</i></b> The aim of this study was to evaluate if the tumor heterogeneity index can predict the aggressiveness of prostate cancer (PCa) in patients diagnosed by magnetic resonance imaging (MRI) fusion biopsy. <b><i>Material and Methods:</i></b> Patients who underwent MRI fusion prostatic biopsy between July 2019 and December 2020 were retrospectively reviewed. Tumor heterogeneity index (coefficient of variation [CV]) and PI-RADS v2.1 sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the last few decades, more recent models, e.g., the CAPRA score, have been developed to replace older methods, such as the Kattan nomograms and Han tables (8,16,19,20). Researchers have also attempted to strengthen such models by integrating the findings from the developing mpMRI technology and molecular evaluations (10,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, more recent models, e.g., the CAPRA score, have been developed to replace older methods, such as the Kattan nomograms and Han tables (8,16,19,20). Researchers have also attempted to strengthen such models by integrating the findings from the developing mpMRI technology and molecular evaluations (10,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…And we can protect these patients' groups from the possible morbidity of radical prostatectomy, such as incontinence, by choosing a more conservative treatment plan. In a recent study, Sokmen et al (29) found that the ADC coefficient of variation value as a tissue texture parameter can be a new biomarker to assess tumor aggressiveness in patients with PCa.…”
Section: Table 3 the Asssociation Between Adc Values And Isup Gradesmentioning
confidence: 99%